Increased efficacy of a dendritic cell–based therapeutic cancer vaccine with adenosine receptor antagonist and CD73 inhibitor. Issue 3 (March 2017) - Arab, Samaneh; Kheshtchin, Nasim; Ajami, Maryam; Ashurpoor, Mahbubeh; Safvati, Aida; Namdar, Afshin; Mirzaei, Reza; Mousavi Niri, Neda; Jadidi-Niaragh, Farhad; Ghahremani, Mohammad Hossein; Hadjati, Jamshid
Dendritic cells are important in initiating immune responses; therefore, a range of dendritic cell–based approaches have been established to induce immune response against cancer cells. However, the presence of immunosuppressive mediators such as adenosine in the tumor microenvironment reduces the efficacy of dendritic cell–based cancer immunotherapy. In this study, we investigated whether blockade of the A2A adenosine receptor with a selective antagonist and a CD73 inhibitor may increase the efficacy of a dendritic cell–based cancer vaccine. According to the findings, this therapeutic combination reduced tumor growth, prolonged survival of tumor-bearing mice, and enhanced specific antitumor immune responses. Thus, we suggest that targeting cancer-derived adenosine improves the outcomes of dendritic cell–based cancer immunotherapy.